2002
DOI: 10.1017/s0967026202003608
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Pseudo-nitzschia multistriata (Bacillariophyceae) from the Gulf of Naples: morphology, toxin analysis and phylogenetic relationships with other Pseudo-nitzschia species

Abstract: The genus Pseudo-nitzschia includes a number of species responsible for blooms in coastal and open waters worldwide. P. delicatissima, a species reported as a potential source of amnesic shellfish poisoning (ASP), reaches high concentrations in the Gulf of Naples (Mediterranean Sea), where it regularly blooms in spring and, at times, in autumn. We assessed both intra-and interindividual genetic diversity of this species before and during a bloom (February to April 2001) by sequencing the internal transcribed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
2
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 76 publications
7
88
2
8
Order By: Relevance
“…OUNISSI & FRÉHI (1999) reported high abundances of Pseudo-nitzschia multiseries (>1000 cells ml -1 ) on the eastern coast of Algeria. Recently, ORSINI et al (2002) confirmed the presence of toxic species of Pseudo-nitzschia in the Tyrrhenian coasts. This genus requires further investigation in the Bay of Tunis.…”
Section: Species Response To Nutrient Variabilitymentioning
confidence: 82%
“…OUNISSI & FRÉHI (1999) reported high abundances of Pseudo-nitzschia multiseries (>1000 cells ml -1 ) on the eastern coast of Algeria. Recently, ORSINI et al (2002) confirmed the presence of toxic species of Pseudo-nitzschia in the Tyrrhenian coasts. This genus requires further investigation in the Bay of Tunis.…”
Section: Species Response To Nutrient Variabilitymentioning
confidence: 82%
“…The toxin has now been detected in shellfish from many European countries, particularly UK, Ireland and France (EFSA, 2009). European strains of several Pseudo-nitzschia species have been found to be toxic: P. australis, P. calliantha, P. galaxiae, P. multiseries, P. multistriata, P. pseudodelicatissima, P. pungens and P. seriata (Table 3; Lundholm et al, 1994;Sarno and Dahlmann, 2000;Cusack et al, 2002;Orsini et al, 2002;Fehling et al, 2004a,b;Moschandreou et al, 2010;E. Keady, pers.…”
Section: Europementioning
confidence: 99%
“…calliantha, P. delicatissima, P. fraudulenta, P. multistriata, P. pungens, P. galaxiae, P. cacciantha, P. mannii, P. arenysensis (QUIJANO-SCHEGGIA et al 2008 and P. australis (ZAPATA et al 2011). In Italy, P. calliantha and P. delicatissima (CAROPPO et al 2005, ZINGONE et al 2006, P. galaxiae, P. multistriata (SARNO and DAHLMANN 2000), ORSINI et al 2002, CERINO et al 2005, ZINGONE et al 2006, P. fraudulenta (ZINGONE et al 2006) were identified. Pseudo-nitzschia calliantha (SPATHARIS et al 2007) was identified in Greece.…”
Section: Introductionmentioning
confidence: 99%